A large-scale nutrition- and gender-sensitive poultry market-based program did not improve maternal and child diets in rural Burkina Faso: A cluster-randomized controlled trial - Becquey, Elodie; Diop, Loty; Diatta, Ampa Dogui; Pedehombga, Abdoulaye; Awonon, Josue; Ganaba, Rasmane; Gelli, Aulo (Elsevier, 2025)
Background Livestock production interventions can improve consumption of animal-source foods and diet diversity, which may lead to improved micronutrient adequacy.